Analisis Rantai Pasok Cabai Rawit dan Upaya Peningkatan Efisiensi di Kecamatan Banyuputih - Hanafi, Mohammad; Aji, Joni Murti Mulyo; Sudarko, Sudarko (Universitas Galuh, 2024)
Cayenne pepper production in Indonesia has continued to increase over the last five years. During the 2016-2020 period, the average increase in cayenne pepper production was 13.6% per year. The island of Java is the largest production center for cayenne pepper in Indonesia, while consumers of cayenne pepper are spread throughout Indonesia. This research aims to analyze the condition of supply chain management and the level of efficiency of supply chain management for cayenne pepper commodities in Banyuputih District. The research method used is descriptive analytical. The respondents in this research were 74 respondents in Banyuputih District who were determined using the Slovin formula technique. The data obtained was analyzed using descriptive analytical methods using the Food Supply Chain Networks approach, marketing margin, Farmer's Share, and marketing efficiency. The research results show: (1) The market share for sales of cayenne pepper in Banyuputih District is divided into several market segments, including local markets and regional markets. (2) the largest marketing margin for cayenne pepper is in marketing channel three, namely 31,000. This channel has the longest supply chain channel for distributing cayenne pepper to farmers. The highest farmer share value is in the first channel where cayenne pepper farmers in Banyuputih District sell directly to end consumers without going through other structures. There are two marketing channels that fall into the efficient category, namely marketing channel 1 and marketing channel 2, while marketing channel 3 has a marketing efficiency value of 34% and is in the less efficient category.